2010
DOI: 10.3945/jn.110.124891
|View full text |Cite
|
Sign up to set email alerts
|

Daily Supplementation with 25 µg Cholecalciferol Does Not Increase Calcium Absorption or Skeletal Retention in Adolescent Girls with Low Serum 25-Hydroxyvitamin D

Abstract: In healthy adolescents, cross-sectional studies show either no or negative relationships between serum 25-hydroxyvitamin D [25(OH)D] and calcium (Ca) absorption. Using a 2-period metabolic balance study, the effect of vitamin D supplementation on Ca absorption and retention in adolescent girls was investigated. Eleven girls aged 12-14 y with a mean entry serum 25(OH)D of 35.1 nmol/L consumed a controlled intake (providing 5 μg vitamin D and 1117 mg Ca/d) for two 3-wk metabolic balance periods separated by a 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 42 publications
3
29
1
1
Order By: Relevance
“…In a posthoc analysis, the observed increase in 1,25(OH) 2 (37)(38)(39)(40)(41)(42)(43)(44). Comparisons between those reports and our findings are made difficult by differences in study design that include the ages of the subjects, type and dose of vitamin D administered, duration of vitamin D administration, baseline 25OHD levels, and assays used.…”
Section: Discussionmentioning
confidence: 40%
“…In a posthoc analysis, the observed increase in 1,25(OH) 2 (37)(38)(39)(40)(41)(42)(43)(44). Comparisons between those reports and our findings are made difficult by differences in study design that include the ages of the subjects, type and dose of vitamin D administered, duration of vitamin D administration, baseline 25OHD levels, and assays used.…”
Section: Discussionmentioning
confidence: 40%
“…42,50,75,79,84,108 As shown in Fig 2, none of the arms achieved a group 25(OH)D level .75 nmol/L with the first measurement, and 2 (33%) achieved this target within the first month. A single weekly dosing regimen was identified that enrolled VDD children and performed blood work within 1 month; this study reported an increase in 25(OH)D from 22 to 143 nmol/L with 4 weekly doses of 60 000 IU.…”
Section: Evaluation Of 25(oh)d Response By Dosing Regimenmentioning
confidence: 99%
“…7 Overall, the results strongly advise that this approach will not normalize levels (.75 nmol/L) in a time frame appropriate to potentially benefit acute and critically ill populations. 42,50,75,79,84,108 These findings are important because they will inform future studies and help in the understanding of the results of published RCTs. For example, these findings might call into question the validity of the pediatric RCT by Choudhary and Gupta 114 evaluating the effect of 5 days of vitamin D (1000-2000 IU/day) on recovery from pneumonia.…”
mentioning
confidence: 99%
“…This is complicated by the fact that serum 25(OH)D is unrelated or negatively related to calcium absorption or retention, at least in healthy Northern American children (5,46). Vitamin D supplementation at 1,000 IU/day for 4 weeks actually decreased calcium absorption despite increasing serum 25(OH)D (47). The systematic reviews used by the IOM concluded that there is no evidence to link vitamin D status and positive changes in bone health outcomes in young children, and only fair evidence in older children and adolescents (4,48).…”
Section: Childhood and Adolescencementioning
confidence: 99%